RANCANGAN BANGUN E-TICKET BIOSKOP DENGAN METODE WATERFALL BERBASIS WEB - Jeperson Hutahaean; Evi Ariyanti Purba (RJOCS (Riau Journal of Computer Science), 2016)
In the application the author made this has a special role in the field of online sales which websites the author designed using programming languages adobe Dremweaver C3 andsoftware xampp as a database on the website writer for this, the working system of the e-cinema tickets online if client wanted to buy a ticket from the filming schedule consumers should clickon the cover of the menu of movies and will appear bio film's content and transfer the money to a bank that has been addressed then the consumer will be given a password and then input thepassword to the e-tickets for the cinema, the ticket can be printed or in print if your data was already in the validation admin.